Nordic capitalisms and globalization new forms of economic organization and welfare institutions - Kristensen, Peer Hull.; Lilja, Kari. (Oxford : Oxford University Press, 2011)
Through detailed case studies of Finland, Denmark, Norway and Sweden, this book investigates how and why welfare services active labour market institutions and public policies were re-combined to stimulate innovation and growth in the Nordic countries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic development -- Scandinavia -- Case studies; Capitalism -- Scandinavia -- Case studies; Globalization -- Economic aspects -- Scandinavia; Scandinavia -- Economic conditions